Supply chain management in footwear industries: supply management of Apex Footwear Ltd. (Unit2) - Mondal, Surojit (Brac University, 2023)
This internship report is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2023.